PTH-131 Umbilical hernia repair in cirrhosis: outcomes and prognostic factors in a liver transplant unit. (22nd June 2015) - John, S; Burnell, P; Robinson, S; Masson, S; Sen, G; Hudson, M; Manas, D
Abstract : Introduction: Patients with end stage liver disease (ESLD) carry a significant risk of adverse outcome after abdominal wall hernia repair, particularly with emergent surgery. Historically, high morbidity and mortality rates have been reported in this cohort. Here, we aim to assess the main predictors for mortality in our own group of high-risk ESLD patients undergoing umbilical hernia repair Method: We performed a retrospective review of a prospectively maintained database of patients with ESLD undergoing surgical repair of complicated umbilical hernias at a regional liver transplant unit over a 15-year period (1999 to 2014). Two third of the patients were operated in the last 6 years. Patient characteristics and outcomes have been analysed and p < 0.05 was considered significant (SPSS vs.19). Results: In total, 69 patients underwent surgical repair (M-52; F-17) at a median age of 58 years (19–88). Of these, 71% were operated on emergently due to incarceration/strangulation or rupture. The patients' Childs-Pugh grade was A (n = 11; 16%), B (n = 32, 46%) and C (n = 26, 38%); the majority (71%) had ascites. The median MELD score was 12 (2–36) and median UKELD was 53(45–63). Postoperatively, 43% patients required ITU care with median LOS 2 days (1–13) and median hospital stay of 11 days (1–73). Postoperative decompensation occurred in 79% of patients, with 26% subsequently requiring liver transplantation in follow-up. At 120 days, the rate of mortality or transplantation was 19%. Overall mortality was 30% at a median follow-up of 35 months (1–160 months). Following univariate logistic regression analysis, Childs-Pugh Grade C, requirement for ITU care, post-operative decompensation and hepatic encephalopathy were significant for prediction of mortality or transplantation at 120 days. After multivariate analysis, only hepatic encephalopathy remained significant, with an odds ratio of 7.04 (p = 0.04). Conclusion: In this series of patients with ESLD, emergent surgical repair of complicated umbilical hernias was associated with significant morbidity and mortality. In our series, development of post-operative encephalopathy was an independent predictor of mortality. This may reflect the late presentation (71% emergent surgery) and high rate of C-P C patients in this cohort. Disclosure of interest: None Declared.